Green Culture and Training on Employee Green Behavior: The Mediating Environmental Awareness Role - Anastasia Puji Renaningtyas; Kasmir Kasmir (Journal of Sustainable Economic and Business, 2026)
Objectives: This study aims to analyze and empirically test the influence of Green Organizational Culture and Training on Employee Green Behavior, both directly and indirectly, with Environmental Awareness as a mediating variable. Methodology: The study employs a quantitative approach with a causal design. The research population consists of 195 Civil Servants within the Agency for Standardization and Industrial Services Policy (BSKJI) and the Industrial Human Resources Development Agency (BPSDMI), with a sample of 133 respondents selected through proportionate stratified random sampling. Data were collected using questionnaires and analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method via SmartPLS 4. Finding: The results demonstrate that Green Organizational Culture and Training have a positive and significant effect on Employee Green Behavior. Furthermore, Environmental Awareness is proven to serve as a mediating variable that strengthens the influence of Green Organizational Culture and Training on Employee Green Behavior Conclusion: This study demonstrates that while Green Organizational Culture does not directly impact Employee Green Behavior significantly, Training and Environmental Awareness do. Crucially, Environmental Awareness serves as a vital mediator, bridging both Green Culture and Training to foster eco-friendly behavior. These findings suggest that the Ministry of Industry should prioritize intrinsic environmental consciousness to translate organizational initiatives into actual green actions.